Experimental Hyperphenylalaninemia in the Pregnant and Nonpregnant Guinea Pig - Kronick, Bernard Jonathan (My University, 1979)
Phenylketonuria (PKU) is an inherited disorder of amino acid metabolism in which the conversion of L-phenylalanine (Phe) to L-tyrosine (Tyr) is greatly diminished. This metabolic block results in high blood Phe levels with low to normal Tyr levels and is usually accompanied by mental retardation unless the disease is treated by dietary restriction of Phe early in life. In recent years it has become apparent that many of the non-PKU offspring of PKU women are damaged in utero by their mother's disease. Approximately 90% of the non-PKU children of PKU mothers are mentally retarded, over 50% are microcephalic and suffer intrauterine growth retardation, while nearly 40% have some congenital malformation. The risk to the offspring of women with hyperphenylalaninemia (hyperphe) probably decreases as the maternal Phe level decreases, althought the "safe" level of maternal hyperphe is not yet well defined. It does appear however, that the developing offspring of women with Phe levels of at least 15 mg/100 ml face substantial risk of in utero damage. Attempts to prevent offspring damage by treatment of pregnant hyperphe women with dietary restriction of Phe have had only limited success. There are still many unanswered questions regarding the management of maternal hyperphe and these will become even more pressing as increasing numbers of PKU women who were success fully treated as children reach reproductive age. Since clinical data are limited attempts have been made to establish experimental animal models of maternal hyperphe.
Early animal studies produced maternal hyperphe by administering large doses of Phe to pregnant animals. Although some of these studies suggested associations between maternal hyperphe and behavioral and biochemical abnormalities found in the offspring, most were confounded by maternal hypertyrosinemia, an abnormality never found in PKU. More recent approaches have utilized the Phe hydroxylase inhibitor p-chlorophenylalanine (pCPA) in order to prevent Tyr elevation following Phe administration. Experiments using both Phe and pCPA administration have more closely mimicked the biochemical characteristics of PKU, however methodological problems have limited the interpretation of many of these studies. In addition, the work with combined Phe and pCPA treatment has been restricted to the rat, a species in which significant differences from human prenatal development exist. The prenatal development of the guinea pig is more similar to man, especially with respect to the brain, and a study was therefore undertaken to determine the suitability of the guinea pig as a possible model of maternal hyperphe. Initially guinea pigs were injected with various regimens of Phe and pCPA. Blood Phe was transiently elevated to levels comparable to those found in PKU patients, however even following very high doses of both Phe and pCPA, Phe fell to near-normal levels within 10 hours of the Phe injection. The blood Phe response of the animals injected with pCPA suggested that the Phehydroxylase inhibition induced by pCPA in guinea pigs is of a much shorter duration than has been reported in rats. Since Phe does not fall to normal levels at any time in untreated PKU, other methods of administering pCPA and Phe were evaluated. Studies were undertaken in which both Phe and pCPA were incorporated into test diets and then fed to guinea pigs. This approach resulted in hyperphe comparable to that associated with significant risk to the human fetus which could be maintained for many weeks in both pregnant and nonpregnant animals. The optimum dietary pCPA supplement was determined by maximizing hepatic Phe hydroxylase inhibition and plasma Phe concentration. The amount of pCPA required to maximally decrease Phe hydroxylase activity in guinea pigs is considerably more than is needed in the rat. Indirect evidence was obtained which suggests that this species difference may be due, at least in part, to rapid excretion of pCPA as p-chlorophenylpyruvic acid by the guinea pig. The appropriate dietary Phe supplement was determined by monitoring plasma Phe and Tyr levels as well as food intake and weight gain in animals fed test diets supplemented with pCPA and various amounts of Phe. Additional work demonstrated that plasma Phe levels remained elevated for at least a 12 hour period during a single day and that ascorbic acid is needed for guinea pigs to efficiently metabolize Tyr.
When stable maternal hyperphe was induced by feeding pregnant guinea pigs appropriate test diets, abortion occurred and was found to be related to pCPA, even in the absence of substantial hyperphe. Further study of the effects of pCPA and hyperphe during early pregnancy was undertaken by feeding guinea pigs test diets from day 1 of pregnancy and collecting embryos on gestation day 17. Only7. Only pCPA was associated with embryonic death, however malformed embryos were significantly associated with maternal hyperphe, even in the absence of pCPA administration. The relationship between maternal hyperphe and malformed embryos had not been previously demonstrated in animals and it may have relevance to the high frequency of congenital defects found in offspring of PKU women. Evidence of embryonic developmental retardation was also found and hyperphe may be causally related to this abnormality as well. Both Phe and Tyr were found to be actively transported to the early embryo and this transport of Phe might be related to its teratogenicity. The embryo toxicity of pCPA limits the utility of the current approach. Use of newer Phe hydroxylase inhibitors in pregnant guinea pigs may prove informative.
Keywords: Medical Sciences; Medical Sciences